PENGARUH PERUBAHAN BENTUK KELEMBAGAAN PROGRAM KB PADA PENGELOLAAN KAMPANYE PROGRAM KB DI TINGKAT FRONTLINER - Djoko Setyabudi; Hapsari Dwiningtyas S; Tandiyo Pradekso (Faculty of Social and Political Sciences, Universitas Diponegoro, 2007)
This research is aimed at examining the effects of the form of family planning institutions on the ways family planning frontliner (PLKB) in Central Java manage their campaign programs. The research findings indicate that the form of family planning institutions, the number of tasks, and incentives given to PLKB, influence the performance of PLKB. another important factor which is significant to the frontliner’s performances is not the form of the institutions, but the way the campaign is managed in each of family planning institution.